Quality of Discovery Learning-Based Chemistry Learning Tools Developed by Chemistry Teacher Candidates - Eda Lolo Allo; Vika Puji Cahyani; Zuhrah Adminira Ruslan (Postgraduate, University of Mataram, 2024)
Prospective chemistry teachers play an important role in implementing Discovery Learning through the learning tools they develop. It is important to evaluate the quality of discovery learning-based learning tools utilised by prospective chemistry teachers in order to provide constructive feedback and improve their competence. This study aims to describe the quality of learning tools in the form of teaching materials and Learner Worksheets that have been prepared by prospective chemistry teachers. This research is a quantitative descriptive research. The population of this study were all students majoring in chemistry class of 2021. This study used purposive sampling technique. The sample of this study was prospective teacher students from the 2021 class B chemistry education study programme, totalling 23 people. Data collection techniques in the form of portfolio/document evaluation in the form of learning devices made by prospective chemistry teacher students. The learning tools collected by prospective teacher students are in the form of teaching materials and student worksheets based on Discovery learning. The learning devices that have been collected are then assessed using validated instruments and assessment rubrics and then scored to determine the ability category of prospective teacher students. The results showed that the quality of discovery learning-based teaching materials prepared by Chemistry teacher candidates in the construction component is categorized as Good, content/material is categorized as Very Good, learning assessment is categorized as Quite Good and discovery learning orientation is categorized as Good. The quality of discovery learning-based student worksheets prepared by prospective chemistry teachers in terms of the construction component is categorized as Very Good, learning activities are categorized as Very Good, learning assessment is categorized as Good and discovery learning orientation is categorized as Very Good.